Healthy Lifestyle, Role Ambiguity, Spiritual Quotient, and Job Burnout on Job Satisfaction - Hermawan, Sigit; Wati, Lina Rahma; Hanif, Aisha; Rahayu, Ruci Arizanda; Rahayu, Duwi (Muhammadiyah International Journal of Economics and Business, 2019)
This study aims to determine the effect of Healthy Lifestyle, Role Ambiguity, Spiritual Quotient and Job Burnout on Job Satisfaction at Public Accounting Firms in Surabaya. The purpose of this study is to analyze the effect of independent variables namely Healthy Lifestyle, Role Ambiguity, Spiritual Quotient and Job Burnout influencing, the dependent variable namely Job Satisfaction assisted by using the SPSS program.  In this study the data were collected through a questionnaire method of 44 respondents by purposive sampling technique to determine the response of respondents to each variable.  Then do the data analysis in the form of quantitative analysis.  Quantitative analysis includes validity and reliability tests, hypothesis testing through the R2 test and T test.  Data analysis techniques using multiple linear regression analysis that serves to prove the research hypothesis. The results of the analysis show that healthy lifestyle, spiritual quotient and job burnout have no partial effect on job satisfaction, while role ambiguity has a partial effect on job satisfaction.